A rapid method for the determination and optimization of kneading consistency

CN122961839APending Publication Date: 2026-10-23ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611169756.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种通过实验室小试快速测定并优化捏合固含的方法,以克服现有技术依赖产线设备、耗时长、物料消耗大且依赖人工经验、精度低的缺陷

Benefits of technology

基于上述机制,浆料达到目标糊状状态后其附着状态和流动状态的保持能力更强,操作者在观察时能够更加直观、快速地作出判断。操作者降低了因判定时机差异导致的测量误差,提高了不同操作人员之间判定结果的一致性。与此同时,整体测定操作时间进一步缩短。由于化学桥接网络的引入,浆料在搅拌与静置过程中的状态稳定性得到提升,使得初测固含与可靠固含之间的对应关系更加明确,步骤一初测值的参考准确性有所提高,步骤二中浆料状态更易接近目标糊状基准,二次调整阶段的操作更为顺畅,单次测定总耗时得到一定压缩。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122961839A_ABST
    Figure CN122961839A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery electrode material preparation, and particularly relates to a kneading solid content rapid determination and optimization method. The method proportionally reduces the production line formula through laboratory small test, adds solvents to the slurry in multiple times to reach the target paste state, and calculates the initial solid content. Then, the target solid content is set, and the calculated solvent is added at one time. The solid content value is adjusted according to the slurry state, and the operation is repeated until the standard is reached, so that the reliable solid content is determined. The application replaces the production line equipment test, shortens the single time consumption from 6-8 hours to 10-20 minutes, reduces the material consumption to the gram level, does not occupy the production equipment, can significantly improve the determination efficiency and accuracy, and reduces the production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery electrode material preparation technology, specifically to a rapid method for determining and optimizing the solid content of kneaded materials. Background Technology

[0002] In the preparation of electrode materials such as lithium-ion batteries, slurry preparation is a crucial preliminary step in electrode manufacturing. The kneading stage significantly impacts the particle size distribution, rheological properties, and subsequent coating quality of the slurry. Kneading solids content is an important process parameter measuring the proportion of solid matter in the slurry during the kneading stage. Excessive solids content can lead to overly dry, clumpy slurry with poor flowability; conversely, insufficient solids content can result in liquid-solid separation and an overly thin slurry. Therefore, accurately measuring and optimizing the kneading solids content is of great significance for ensuring the quality of the electrode slurry.

[0003] Currently, the determination of kneaded solids content largely relies on long-line equipment in production lines. This typically involves gradually adding liquid to a mixing tank and repeatedly sampling, relying on experience to judge the slurry's state until suitable process requirements are met. This method suffers from problems such as long testing cycles, high material consumption, reliance on manual experience, and inconsistent judgment standards among different operators. Furthermore, the testing process occupies production equipment, affecting the normal operation of the production line. While some offline testing methods can operate outside the production line, their testing efficiency remains low, and they struggle to reflect the slurry's state changes during the kneading process in a timely manner.

[0004] Therefore, there is an urgent need to develop a method that can quickly and accurately determine and optimize the kneading solids content under laboratory conditions, so as to improve the determination efficiency, reduce the cost of materials and equipment, and improve the consistency and repeatability of the results. Summary of the Invention

[0005] The purpose of this invention is to provide a method for rapidly determining and optimizing the solid content of kneading through laboratory-scale testing, in order to overcome the shortcomings of existing technologies that rely on production line equipment, are time-consuming, consume large amounts of materials, depend on human experience, and have low precision.

[0006] A rapid method for determining and optimizing the solid content of kneaded materials includes the following steps: Step 1: Take samples proportionally according to the raw material ratio of the production line to obtain pilot raw materials; add solvent to the pilot raw materials in batches in a gradient, and perform stirring and state observation after each addition until the rheological properties of the slurry reach the preset target paste benchmark; calculate the initial solid content X% based on the dry weight of the pilot raw materials and the total amount of solvent added; the pilot raw materials include active main material, conductive agent and binder. Step 2: Using the initial solid content X% as the baseline offset, set the target solid content and inversely calculate the theoretical amount of solvent required to reach the target solid content; add the theoretical amount of solvent to the same mass of the small-scale raw materials as in step 1, stir, and perform state observation again; if the slurry state deviates from the target paste benchmark, perform step-by-step correction on the target solid content according to the actual deviation direction, and repeat the steps of calculating the theoretical amount of solvent, adding, and observing the state based on the corrected solid content until the slurry state reaches the target paste benchmark, and calibrate the current solid content as the reliable solid content Y.

[0007] This invention obtains an initial solids content benchmark through gradient solvent addition and constructs a closed-loop feedback optimization path by combining theoretical solvent addition calculation with a step-by-step correction mechanism. This allows the slurry state to quickly converge to the target paste-like benchmark, significantly reducing both measurement time and cumulative time spent switching between multiple batches. This method replaces traditional manual visual judgment with an objective physical benchmark possessing adhesion, creeping flow characteristics, and macroscopic uniformity. Combined with a step-by-step solids content correction strategy, it narrows the measurement fluctuation range and effectively reduces batch-to-batch quality variations. The entire measurement process is completed on a small-scale laboratory scale, without occupying long-line production equipment. It can operate in parallel with normal production, avoiding capacity loss due to equipment occupation and the risk of restarting due to operational errors. By pre-quantifying the theoretical solvent addition amount through inversion calculation, it avoids irreversible losses of slurry due to empirical step-by-step addition. The consumption of raw materials and solvents in the small-scale test is far lower than in traditional production line modes, significantly reducing material costs. The gradient addition logic of this method can be flexibly adapted according to the liquid absorption characteristics of the powder. It can be extended to oil-based and water-based kneading systems without redesigning the process for different electrode material systems, and has broad industrial application prospects.

[0008] Optionally, in step one, the solvent is added in a gradient batch manner, with the initial addition being 60%–70% of the estimated total solvent mass. The remaining solvent is added in 2–3 batches, with each batch adding 10%–25% of the estimated total solvent mass. This gradient addition strategy, with stirring and state observation performed after each addition, allows the operator to assess the viscosity and flowability of the slurry in real time during each addition cycle. This enables precise control of the total solvent volume, avoiding irreversible losses due to excessive thinning of the slurry caused by a single over-addition. This gradient addition method standardizes the solvent addition process. Compared to the existing technology that relies on manual, step-by-step addition on the production line and lacks clear proportion control, it significantly reduces the initial test failure rate due to insufficient operational experience. It ensures good consistency and repeatability of the slurry paste state obtained in step one, thus providing a reliable solids content benchmark value for secondary adjustments and optimizations in step two, improving the stability and accuracy of the entire measurement method from the source.

[0009] Furthermore, the remaining solvent is added in two batches. The second batch accounts for 20%–25% of the estimated total solvent mass, and the third batch accounts for 10%–15%. This progressively decreasing solvent addition ratio matches the initial rapid-then-slow wetting characteristics of the powder during liquid absorption. The initial high proportion of solvent is used to quickly wet the dry powder and form the basic slurry framework, while subsequent decreasing proportions are used to eliminate residual particle agglomerates and fine-tune the final slurry flowability. This gradient reduction method effectively avoids the defect of localized overwetting due to excessively rapid solvent addition, while also preventing the problems of prolonged operation time and increased material adhesion loss caused by excessive additions. It can stably obtain the target paste-like slurry without lumps or stratification, balancing operational efficiency with the accuracy and repeatability of the initial solids content measurement.

[0010] In step one, the solvent is added in multiple stages in a reverse incremental manner, specifically using a three-stage gradient: the first addition accounts for 15% to 25% of the estimated total solvent mass; The second addition accounts for 25% to 35% of the estimated total solvent mass; The third addition accounts for 40% to 60% of the estimated total solvent mass; This approach, along with the progressively decreasing addition method, constitutes a parallel alternative implementation path. For powder systems with strong liquid absorption and swelling characteristics or those sensitive to initial solvent contact, the sequence of adding small amounts first and then large amounts allows the powder to be gradually wetted in a low-solvent environment. A thin solvent film first forms on the surface of each component particle, and then, as the solvent ratio increases, the slurry system gradually transitions from a loose state to a viscous paste. This process helps avoid the defect of instantaneous overwetting of the powder surface when a high proportion of solvent is initially added, resulting in a viscous coating layer on the outer surface of the particles while the inside still contains dry powder. This is especially suitable for electrode materials such as hard carbon and ceramic powder, which have large differences in liquid absorption rates. The observation process after each addition allows the operator to flexibly judge whether subsequent solvent additions need to be corrected based on the viscosity and dispersion after stirring, expanding the adaptability and applicability to different electrode material systems while maintaining measurement accuracy and success rate.

[0011] Optionally, the target paste-like standard in step one is defined as follows: the slurry adheres to the stirring tool, flows viscously when poured, and is free of lumps and stratification. This defined target paste-like standard provides a clear and objectively verifiable endpoint for the initial solids content calculation and secondary adjustment optimization in this invention. The determination of this state characteristic is based on the fact that the slurry adhering to the stirring tool indicates that the solids content is within a suitable range; the slow, viscous flow when poured indicates that the system has appropriate rheological properties; and the absence of lumps and stratification proves that the solvent has been fully and uniformly mixed with the powder. The establishment of this judgment standard allows operators to accurately identify the moment when the solids content meets the standard without relying on vague subjective experience, effectively eliminating judgment bias caused by individual sensory differences. This significantly improves the accuracy and consistency of the slurry state used for the initial solids content calculation in step one, and provides a unified reference standard for the state comparison after the one-time addition of solvent in step two, ensuring the reliability of the judgment of excessive dryness or excessive thinness during the secondary adjustment process. Meanwhile, the standard is concise and intuitive, making it easy for different operators to quickly master and accurately execute, significantly reducing the difficulty of operation and the probability of measurement failure due to misjudgment of status, thereby improving the repeatability and success rate of the entire measurement method.

[0012] Optionally, in step two, an initial target solid content is set based on the initial solid content X%, preferably an increase of 0.3% to 0.5% above X%. If the slurry state deviates from the target paste-like standard after a one-time addition, the target solid content is corrected in increments of 0.1% to 0.3% according to the direction of deviation, until the slurry state reaches the target paste-like standard.

[0013] Appropriately increasing the target solid content based on the initial solid content helps increase the solid phase ratio and reduce solvent usage in the electrode material kneading process, which is beneficial for reducing energy consumption and improving production efficiency in the subsequent drying process. The setting of this increment value takes into account both optimization efficiency and operational error tolerance. If the increment is too large, it will easily lead to the slurry being too dry and clumping, and it will be difficult to effectively correct it through subsequent fine-tuning. If the increment is too small, it will require repeated adjustments to approach the optimal value, resulting in a decrease in optimization efficiency. However, by using a specific increment value, the state of the slurry after adding solvent can be close to the boundary of the optimal operable range. It can quickly converge to a reliable solid content with one or at most two fine-tunings. This avoids the risk of the slurry being too dry due to excessive increment, which requires resampling and measurement, and also avoids the problem of repeated experiments due to excessive increment, which increases the operation time. This allows step two to complete the rapid convergence from the initial solid content to the reliable solid content with the fewest adjustment rounds, further compressing the overall measurement cycle.

[0014] Optionally, in step two, the step of performing a step-by-step correction of the target solid content based on the actual deviation direction is as follows: if the slurry exhibits clumping, loose granular form, or loses its adhesion to the stirring tool after a one-time addition of solvent, it is determined to be in an over-dry state, and the target solid content needs to be corrected downward by 0.1~0.3%; If the slurry exhibits liquid-solid stratification or free solvent precipitation after a single addition of solvent, it is determined to be in an overly dilute state, and the target solid content needs to be corrected upward by 0.1~0.3%.

[0015] The determination of whether the slurry is too dry or too thin is based on intuitive physical phenomena observed during the mixing process. Agglomeration, loose granules, and failure to adhere to the stirring surface indicate an overly dry state, while liquid-solid separation and free solvent precipitation indicate an overly thin state. Operators can quickly and accurately determine the direction of solid content deviation without the need for instruments, avoiding incorrect adjustments due to ambiguous judgment criteria. The fine-tuning step size is coordinated with the target solid content increment. Since the slurry state usually only shows a slight degree of over-dryness or over-thinness after adding the corresponding target solid content solvent in one go, this step size is sufficient to effectively correct the deviation without overcorrecting due to excessive adjustment, thus avoiding repeated oscillations between over-dryness and over-thinness. This mechanism allows the second step to converge the slurry state to the target paste state with only a few fine-tunings, keeping the secondary adjustment stage time within a few minutes, significantly improving the convergence efficiency of the optimization process, and reducing the material and time losses caused by resampling due to adjustment failures.

[0016] Optionally, in step one, the initially added solvent contains 0.3% to 0.8% of an organosilicon-modified polyether wetting and dispersing agent by the estimated total solvent mass, and this dispersing agent is not added separately in subsequent solvent additions. The organosilicon-modified polyether wetting and dispersing agent has a molecular structure containing siloxane segments and polyether side chains. The siloxane segments can form an adsorption layer with the active sites on the powder surface, while the polyether side chains form a steric barrier in the solvent, weakening the van der Waals attraction between particles. This structure can reduce the surface tension at the solid-liquid interface, improve the solvent's ability to simultaneously wet the dry powder, and eliminate the phenomenon of dry powder sandwiching and local agglomeration within the powder. Adding the dispersing agent only to the initial solvent system can maintain a uniform powder wetting rate throughout the process, reduce the state deviation range corresponding to the visual judgment standard of the slurry, stabilize the fluctuation of the initial solid content calculation value, and control the fluctuation range of the solid content measurement within 0.1%. The standardized wetting process reduces the time required for stirring and homogenization, shortening the overall measurement process by two to six minutes. At the same time, it is compatible with both forward and reverse stepwise liquid addition modes, improving the method's versatility for electrode powders with different liquid absorption characteristics.

[0017] Optionally, the binder is an oil-based compound binder system, composed of polyvinylidene fluoride (PVDF) and polyimide (PI) powder; the mass ratio of PVDF to PI powder is 7.5:2.5 to 8.5:1.5, and the total mass of the binder accounts for 4.5% to 5.5% of the total mass of the raw materials in the pilot test. PVDF molecules have excellent compatibility with NMP solvent, providing basic bonding strength. The rigid molecular segments of polyimide are blended with PVDF to form a polymeric blend system. The composite binder system can buffer the difference in solvent absorption rates between the active powder and the conductive agent, broaden the stable viscoelastic range of the slurry, and weaken the abrupt changes in slurry state caused by small fluctuations in solvent addition. Within this ratio range, the polymeric network can suppress the tendency of the slurry to become too dry and agglomerate or too thin and separate, reducing the number of solid content fine-tuning operations in the secondary optimization stage and improving the efficiency of reliable solid content determination. The total proportion range of the binder matches the conventional cathode formulation system of the production line, improving the consistency between the rheological properties of the pilot test slurry and the mass production slurry, and reducing the deviation when scaling up the solid content calculation results from the pilot test to the production line.

[0018] Optionally, the binder is an aqueous compound binder system, composed of sodium carboxymethyl cellulose (CMC) and sodium alginate powder; the mass ratio of CMC to sodium alginate powder is 6.5:3.5 to 7.5:2.5, and the total mass of the binder accounts for 4.5% to 5.5% of the total mass of the raw materials in the pilot test. Sodium carboxymethyl cellulose molecules carry a large number of carboxyl groups, enabling basic dispersion and bonding of the powder; sodium alginate molecules are rich in hydroxyl and carboxyl groups. After compounding, the molecular chains form a physical cross-linking network through hydrogen bonding and electrostatic interactions. This composite binder system can balance the water absorption rate of hard carbon anode powder, suppress liquid-solid stratification caused by localized solvent enrichment, and inhibit agglomeration caused by uneven liquid absorption of the powder. This ratio range can smooth the fluctuation range of the slurry rheological properties with changes in solid content, reducing the probability of repeated fine-tuning of solid content during the secondary optimization stage. The total mass percentage range of the binder is adapted to the formulation range of sodium-ion battery anode mass production. The rheological behavior of the small-scale slurry is better matched with that of the production line slurry. When the solid content calculation value is scaled up to the production stage, the deviation is effectively suppressed.

[0019] Optionally, in step one, when adding solvent in multiple batches, a silane coupling agent is mixed into the solvent added in the first batch. The silane coupling agent is selected from γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, and its addition amount is 0.1% to 0.5% of the total mass of the raw materials in the pilot test. The solvent is deionized water or an aqueous solvent system.

[0020] After the silane coupling agent is mixed into the deionized water solvent added in step one, the alkoxy group at one end of the silane coupling agent hydrolyzes in the aqueous system to generate silanol groups, which then undergo a condensation reaction with the hydroxyl groups on the surface of the active material particles to form chemical bonds. The organic functional groups at the other end undergo a coupling reaction with the binder molecular chains, forming a particle-coupling agent-binder chemical bridging network in situ within the slurry system. This chemical bridging network maintains good fluidity and workability of the slurry under stirring shear forces, and the network structure recovers and stabilizes the slurry state under static observation. Based on the above mechanism, the slurry maintains its adhesion and flow states more effectively after reaching the target paste state, allowing operators to make more intuitive and rapid judgments. This reduces measurement errors caused by differences in judgment timing and improves the consistency of judgment results among different operators. Simultaneously, the overall measurement operation time is further shortened. Due to the introduction of the chemical bridging network, the stability of the slurry's state during stirring and settling is enhanced, making the correspondence between the initial solids content and the reliable solids content clearer. The reference accuracy of the initial measurement value in step one is improved, the slurry state in step two is more likely to approach the target paste benchmark, the operation of the secondary adjustment stage is smoother, and the total time for a single measurement is reduced to some extent.

[0021] The advantages of this invention are as follows: the measurement cycle is significantly shortened from the original long operation time, efficiency is increased by tens of times, and the cumulative time consumption during multiple batch switching is significantly reduced; the pilot test process requires only trace amounts of raw materials and solvents, the material consumption of a single experiment is extremely low, and it does not require occupying long-line production equipment. The measurement can be completed simultaneously while the production line is running normally, effectively ensuring continuous production efficiency, while avoiding the production cycle extension caused by the need to empty the equipment and re-feed materials due to operation failure; more importantly, this method replaces traditional manual experience judgment with standardized step-by-step solvent addition and clear target paste state judgment criteria, which significantly improves the measurement accuracy, effectively ensures batch-to-batch consistency, and reduces the skill requirements of operators, making it easy to promote and apply in the industry. Attached Figure Description

[0022] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0023] Figure 1 This is a schematic diagram of the state of the over-dried slurry of the present invention.

[0024] Figure 2 This is a schematic diagram of the standard target paste-like slurry state of the present invention.

[0025] Figure 3 This is a schematic diagram of the diluted slurry of the present invention.

[0026] Figure 4 This is a comparison chart of the fluctuation range of solid content determination in each embodiment and test group.

[0027] Figure 5 A comparison chart showing the optimized total time for kneading solids content determination in various embodiments and experimental groups. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] The concepts involved in this application will first be described with reference to the accompanying drawings. It should be noted that the following descriptions of various concepts are only for the purpose of making the content of this application easier to understand and do not constitute a limitation on the scope of protection of this application; furthermore, the embodiments and features in the embodiments of this application can be combined with each other unless otherwise specified. This application will now be described in detail with reference to the accompanying drawings and embodiments.

[0030] To facilitate understanding of this invention, the following explanations are provided for the English abbreviations appearing in the specification: PVDF: Polyvinylidene fluoride; PI: Polyimide; CMC: Sodium carboxymethyl cellulose; NMP: N-methylpyrrolidone.

[0031] Unless otherwise stated, the abbreviations mentioned above in this specification refer to the substances represented by their corresponding full Chinese names.

[0032] In Examples 1 and 2, the solid content determination and optimization can be independently completed through process control alone, and these are the basic embodiments of the present invention. Examples 3, 4, and 5 further introduce optional auxiliary components on top of the basic embodiments to improve the wetting and dispersion performance and rheological stability of specific systems, and these are the preferred embodiments of the present invention. The aforementioned basic embodiments and preferred embodiments are parallel and progressive, rather than mutually exclusive.

[0033] Example 1: 1. Initial measurement of kneaded solids content The basic formula for the production line is a mixture of sodium electroactive material layered oxide as the main material, conductive agent carbon black, and binder polyvinylidene fluoride in a mass ratio of 90:5:5. The total amount of material fed into the production line at one time is 100 kg. The laboratory samples were taken in a scaled-down manner according to the production line formula. The total mass of raw materials (including the total mass of active material, conductive agent and binder) in the small-scale test was 10 g, of which 9 g were layered oxide, 0.5 g were carbon black and 0.5 g were polyvinylidene fluoride. This embodiment is adapted to oil-based adhesive systems, using N-methylpyrrolidone as the solvent. Based on the material's liquid absorption characteristics, the estimated total solvent usage is approximately 5g. The solvent is added in three stages, decreasing in quantity from the first to the last: First, 3.5g of solvent is added, accounting for 70% of the estimated total solvent amount. The mixture is manually stirred until the raw materials and solvent are initially mixed, the powder is generally wetted, and agglomerated particles are formed. Second, 1g of solvent is added, accounting for 20% of the estimated total solvent amount. The mixture is stirred until there are no obvious agglomerates in the slurry, and the system becomes relatively uniform. Third, 0.5g of solvent is added, accounting for 10% of the estimated total solvent amount. The mixture is stirred continuously until it forms a uniform paste, reaching the target state, where the slurry adheres to the surface of the stirring tool, flows slowly in a viscous consistency when poured, and there are no lumps or liquid-solid separation.

[0034] Preliminary solids content is calculated according to the solids content definition formula: Preliminary solid content X% = Total mass of raw materials ÷ (Total mass of raw materials + Total mass of solvent) × 100% Substituting the values ​​into the calculation of this embodiment, we get: X% = 10 ÷ (10 + 5) × 100% = 66.7%.

[0035] 2. Secondary adjustments and optimizations Based on the initial solid content of 66.7%, a target solid content of 67.2% was set, increasing by 0.5 percentage points. Let the total solvent amount corresponding to this target solid content be m, and substitute it into the solid content calculation formula to establish the equation: 67.2% = 10 ÷ (10 + m) × 100% The solvent dosage was calculated to be approximately 4.88g. 10g of raw material with the same ratio as described above was taken and 4.88g of N-methylpyrrolidone was added at once and stirred evenly. It was observed that the slurry agglomerated, had poor fluidity, and could not stably adhere to the surface of the stirring tool. It was determined that the slurry was too dry and the current target solid content was too high.

[0036] The target solids content was reduced by 0.3 percentage points to 66.9%, and the corresponding solvent usage was recalculated by substituting the values ​​back into the solids content formula: 66.9% = 10 ÷ (10 + m) × 100% The solvent usage was calculated to be approximately 4.95 g. 10 g of the initial raw material was taken and 4.95 g of N-methylpyrrolidone was added at once. After stirring thoroughly, the slurry reached the target paste-like state, consistent with the initial determination criteria. The reliable solid content Y% of this material system was ultimately determined to be 66.9%. To further verify the repeatability and stability of the method in this embodiment, five parallel experiments were conducted independently using the same raw material system, ratio, solvent type, and step-by-step addition process as described above. Each experiment successfully obtained the target paste-like slurry and completed the initial solid content determination and secondary adjustment optimization. The final reliable solid contents were 66.9%, 67.0%, 66.8%, 66.9%, and 67.0%, respectively, with an arithmetic mean of 66.9% and a fluctuation range of 0.2%, indicating that the method has good repeatability and consistency in this system. The average total time for each of the five parallel experiments was approximately 18 minutes, further demonstrating that this invention can rapidly complete the determination and optimization of kneading solid content under laboratory-scale conditions.

[0037] When scaling up production lines, the feeding parameters can be directly calculated based on the reliable solid content. The calculation formula is: Total solvent = Total raw material feeding amount of production line ÷ Y% - Total raw material feeding amount of production line; based on a single feeding amount of 100kg of raw material in the production line, the corresponding total solvent amount is approximately 49.5kg.

[0038] Example 2: This embodiment employs a reverse incremental solvent addition method to measure the performance of a sodium battery hard carbon anode material system with strong liquid absorption and expansion characteristics. The raw material ratio, solid content measurement calculation formula, and secondary adjustment logic are completely consistent with those in Example 1, except that the solvent addition order is changed from "more first, less later" to "less first, more later".

[0039] Specifically, a 10g sample was taken according to the ratio of hard carbon:carbon black:CMC = 90:5:5, and the estimated total amount of deionized water was 4.5g. The amounts added in three batches were 1.0g, 1.5g, and 2.0g respectively, with stirring and observation after each addition. The final slurry reached the target paste-like state. Substituting into the solids content formula, the initial solids content X was determined to be 69.0%.

[0040] Based on an initial solids content of 69.0%, the target solids content was initially set at 69.3%, and the corresponding theoretical water addition was calculated. After adding the calculated total amount of deionized water at this solids content in one go, the slurry mixing results showed that the system was slightly dry, with some fine particles not fully expanded, but still exhibiting a certain degree of adhesion, indicating slight over-dryness. Considering the small deviation, the target solids content was further reduced by 0.1% to 69.2%, and the corresponding theoretical water addition was recalculated and added in one go. Usually, a uniform paste state can be achieved after one stirring. Adhesion, fluidity, and macroscopic uniformity all met the target paste benchmark, and the reliable solids content of the system was determined to be 69.2%.

[0041] Five parallel experiments were conducted independently under the above conditions, with an average total time of approximately 18 minutes per experiment. The reliable solid contents measured were 69.3%, 69.1%, 69.2%, 69.0%, and 69.3%, respectively, with an arithmetic mean of 69.2% and a fluctuation range of 0.3%. This indicates that the method has good repeatability and stability in a hard carbon aqueous system. The conversion method for production line scale-up is the same as in Example 1. This scheme is particularly suitable for material systems with large differences in liquid absorption rates, such as hard carbon and ceramic powder.

[0042] Sample Example 1: This sample example uses the same sodium battery layered oxide cathode material system as Example 1. The raw materials are compounded in a mass ratio of 90:5:5 for the layered oxide main material, conductive agent carbon black, and binder polyvinylidene fluoride. Each sample takes 10g of the total mass of raw materials. Using N-methylpyrrolidone as solvent, three groups of slurry samples with different solid contents are prepared by adjusting the amount of solvent added. This is used to clarify the judgment boundary of the target paste state and to visually present the morphological differences of the three states of high, optimal, and low solid content.

[0043] The optimal solids content sample corresponds to a reliable solids content of 66.9%. After adding 4.95g of solvent, the slurry exhibits a uniform paste-like consistency after thorough stirring. It can stably adhere to the surface of the stirring tool and flows slowly in a continuous viscous state when poured. There are no lumps or liquid-solid stratification in the system, which is the ideal state for the kneading process, i.e., the target paste-like state for determining that the solids content meets the standard in the method of this invention.

[0044] The sample with high solids content corresponds to a solids content of 67.2%. After adding 4.88g of solvent, the slurry was generally dry after stirring, with obvious lumps and loose particles. It could not continuously adhere to the surface of the stirring tool, and the rheology was poor and it was in a discontinuous flow state, indicating that the amount of solvent added was insufficient and the solids content exceeded the reasonable process range.

[0045] The sample with low solid content corresponds to a solid content of 65.0%. Approximately 5.38g of solvent was added. After stirring, the slurry was generally thin and soft. When poured, it flowed rapidly in a liquid state. Only a very thin layer of slurry remained on the surface of the stirring tool. After standing, liquid-solid separation and free solvent precipitation easily occurred, indicating that the solvent was added in excess and the solid content was lower than the reasonable process range.

[0046] By comparing the states of three sets of samples, a standardized visual judgment standard can be established, eliminating judgment errors caused by differences in human experience, ensuring the consistency and repeatability of solid content judgment in the initial and optimization stages, and providing a unified state reference standard for the entire measurement method.

[0047] Comparative Example 1: This comparative example uses industrial long-line production equipment for kneading solids content determination. The raw material system used is the same as that in Example 1. The main material is sodium battery layered oxide, the conductive agent is carbon black, and the binder is polyvinylidene fluoride. The mass ratio of the three is 90:5:5, and the total mass of raw materials fed into the production line at one time is 100 kg.

[0048] The determination process was completed in the production line's mixing unit. After all the dry powder raw materials were added to the mixing vessel, N-methylpyrrolidone solvent was gradually added while the mixer was turned on and continuously stirred at the set speed. During the operation, the operator stopped the machine multiple times to take samples, visually observing the viscosity and dispersion of the slurry based on experience, and repeatedly adjusting the amount of solvent added and the mixing parameters until it was determined that the slurry had reached a suitable kneading state. After final weighing, the total amount of solvent added was approximately 49.5 kg, and the measured solid content was approximately 66.9% according to the solid content definition formula.

[0049] The entire solids content determination process for this comparative example takes approximately 7 hours. The determination process requires repeated starting and stopping of the production line equipment. If excessive solvent is added or the stirring parameters are out of control, resulting in abnormal slurry conditions, the equipment must be emptied and materials re-added, further extending the cycle. Each determination consumes 100 kg of raw materials and tens of liters of solvent, resulting in high material costs. The determination of the endpoint relies on manual experience, and the solids content determination error can reach ±1% or more, leading to significant batch-to-batch quality fluctuations. Furthermore, the determination process occupies long production lines, preventing normal production operations. When switching between multiple batches of materials, the cumulative downtime can reach several days, severely impacting continuous production efficiency.

[0050] Example 3: This embodiment adjusts the basic process of Example 1, still using an oil-based kneading system, but replaces the binder with a PVDF and PI compound binder system (mass ratio 8:2, total binder mass accounts for 5% of the total mass of raw materials in the pilot test). The solvent type (NMP), step-by-step liquid addition method and solid content optimization process are consistent with Example 1, and the effect of compound polymer network on improving slurry rheology is verified separately.

[0051] The total mass of raw materials for the small-scale test was 10g (9g layered oxide, 0.5g carbon black, and 0.5g compound binder). The estimated total amount of N-methylpyrrolidone was 5g, and no wetting or dispersing agent was added. After adding the liquid in three steps, 60% (3.0g) of the estimated total amount was added for the first step, 25% (1.25g) for the second step, and 15% (0.75g) for the third step. The slurry reached the target paste-like state, and the initial solid content X was calculated to be 66.7%.

[0052] In the second adjustment stage, the target solids content was set at 67.0%, corresponding to a solvent dosage of approximately 4.90g. After adding the solvent all at once and stirring, the slurry only showed slightly loose particles and did not form obvious large-area lumps, indicating it was slightly too dry. The target solids content was then lowered by 0.1% to 66.9%, corresponding to a solvent dosage of approximately 4.95g. After adding the solvent again and stirring, the slurry directly met the target, requiring no further fine-tuning.

[0053] Five parallel tests were conducted independently under the above conditions, with an average time of 13 minutes. The reliable solid content measured in this group was 66.9%, 66.8%, 66.9%, 67.0%, and 66.9%, respectively, with an arithmetic mean of 66.9% and a fluctuation range of 0.2%. The conversion method for production line scale-up was the same as in Example 1. The results show that the PVDF / PI compound system, by forming a synergistic bonding network, makes it easier for the slurry to reach the target paste state, and the secondary adjustment range is smaller than that in Example 1.

[0054] Example 4: This embodiment upgrades the basic process of Example 2, targeting the sodium battery hard carbon anode material system with strong liquid absorption and expansion characteristics. It introduces an organosilicon-modified polyether wetting and dispersing agent and a CMC and sodium alginate composite binder. The dispersant is added at 0.5% of the estimated total solvent mass, the CMC to sodium alginate mass ratio is 7:3, and the total mass of the binder accounts for 5% of the total mass of the raw materials in the pilot test. Deionized water is used as the solvent. The solvent addition method and solid content optimization process are consistent with Example 2, and the effect of using the combined wetting and dispersing agent and composite binder on improving the stability of the slurry is verified separately.

[0055] The total mass of raw materials for the small-scale test was 10g (9g hard carbon, 0.5g carbon black, and 0.5g compound binder), with an estimated total deionized water usage of 4.5g. Initially, 1.0g of deionized water was added, along with 0.025g of dispersant. After stirring, the powder was rapidly wetted, and no obvious dry powder inclusions were observed. A second addition of 1.5g of deionized water was made, and after continued stirring, the slurry gradually formed continuous agglomerates. A third addition of 2.0g of deionized water was made, and the slurry finally reached the target paste-like state. The initial solid content X was calculated to be 69.0%.

[0056] Based on an initial solids content of 69.0%, the target solids content was initially set at 69.3%, and the corresponding theoretical water addition was calculated. After adding the calculated total amount of deionized water at this solids content in one go, the slurry mixing results showed that only a very small amount of fine, loose particles appeared in the system, and the adhesion was still good, indicating that it was slightly too dry. Considering that the deviation was small, the target solids content was further reduced by 0.1% to 69.2%, and the corresponding theoretical water addition was recalculated and added in one go. After stirring again, the slurry reached a uniform paste state, and the adhesion, fluidity, and macroscopic uniformity all met the target paste benchmark. The reliable solids content of the system was determined to be 69.2%.

[0057] Five parallel experiments were conducted independently under the above conditions. The reliable solid content measured in this group were 69.2%, 69.2%, 69.1%, 69.2%, and 69.1%, respectively, with an arithmetic mean of 69.2% and a fluctuation range of 0.1%. The average total time was approximately 10 minutes. The results show that the combined use of organosilicon-modified polyether wetting and dispersing agent and CMC / sodium alginate composite binder can significantly improve the wetting consistency and rheological stability of the hard carbon system, and stably control the fluctuation range of the solid content optimization process within ±0.1%. The production line scale-up conversion method is the same as in Example 1.

[0058] Comparative Example 2: This comparative example is the same as Example 4, both using a hard carbon negative electrode aqueous system and a reverse incremental stepwise liquid addition process. However, only a single CMC binder is used, and no organosilicon-modified polyether wetting and dispersing agent is added throughout the process. The total mass of the raw materials in the small-scale test was 10g, the estimated total amount of deionized water was 4.5g, and the initial solid content X after three additions of water was 69.0%.

[0059] In the second adjustment stage, after setting a target solids content of 69.3%, the corresponding solvent was added in one go. The slurry showed noticeable fine agglomerates, indicating it was too dry. The target solids content was then lowered to 69.1% to achieve the desired result. Five parallel tests were conducted under the above conditions, and the reliable solids contents were measured to be 69.1%, 69.0%, 69.2%, 69.1%, and 69.0%, respectively. The arithmetic mean was 69.1%, with a fluctuation range of 0.2%, and the average total time was approximately 18 minutes.

[0060] Compared with Example 4, this comparative example has poorer slurry wetting and rheological stability due to the lack of compound binder and dispersant, and the optimization accuracy and efficiency of solid content are reduced.

[0061] Comparative Example 3: This comparative example is conducted under the same conditions as Comparative Example 2, but with the addition of an organosilicon-modified polyether wetting and dispersing agent at an estimated total solvent mass of 0.5%. The binder remains a single CMC, without the addition of sodium alginate. The total mass of the raw materials for the small-scale test was 10g, and the estimated total amount of deionized water was 4.5g. After three additions of water, the initial solid content X was 69.0%.

[0062] In the second adjustment stage, after setting the target solids content at 69.3%, the corresponding solvent was added in one go. Only a small amount of fine, loose particles appeared in the slurry. After adjusting to 69.2%, the target was met. Five parallel tests were conducted under the above conditions, and the reliable solids contents were measured to be 69.2%, 69.1%, 69.2%, 69.1%, and 69.2%, respectively. The arithmetic mean was 69.2%, the fluctuation range was 0.1%, and the average total time was approximately 13 minutes.

[0063] Compared with Comparative Example 2, the addition of dispersant can significantly improve wetting consistency and homogenization efficiency, but since it is still a single CMC system, its stability is still weaker than that of Example 4.

[0064] Example 5: This embodiment is based on the process of Example 2 with adjustments. In step one, a silane coupling agent is mixed into the deionized water. The silane coupling agent is selected from γ-aminopropyltriethoxysilane and the amount added is 0.3% of the total mass of the raw materials in the small test. The remaining steps are the same as in Example 2.

[0065] The total mass of the raw materials for the small-scale test was 10g, sampled according to the ratio of hard carbon:carbon black:CMC = 90:5:5, with an estimated total amount of deionized water of 4.5g. First, 1.0g of deionized water was added, along with 0.03g of silane coupling agent. After stirring, the powder was uniformly wetted, with no obvious dry powder inclusions. Second, 1.5g of deionized water was added, and after continued stirring, the slurry gradually formed continuous agglomerates. Third, 2.0g of deionized water was added, and the slurry finally reached the target paste-like state. The initial solid content X was calculated to be 69.0%.

[0066] Based on an initial solids content of 69.0%, the target solids content was initially set at 69.3%, and the corresponding theoretical water addition was calculated. After adding the calculated total amount of deionized water at this solids content in one go, the slurry showed only a small amount of fine, loose particles, with acceptable adhesion, indicating slight over-dryness. The target solids content was further reduced by 0.1% to 69.2%, and the corresponding theoretical water addition was recalculated and added in one go. After re-stirring, the slurry reached a homogeneous paste state, and its adhesion, flowability, and macroscopic uniformity all met the target paste benchmark. The reliable solids content of this system was determined to be 69.2%.

[0067] Five parallel experiments were conducted independently under the above conditions. The reliable solid contents measured in this group were 69.2%, 69.2%, 69.1%, 69.2%, and 69.1%, respectively, with an arithmetic mean of 69.2% and a fluctuation range of 0.1%. The average total time was approximately 10 minutes. The results indicate that the introduction of a silane coupling agent into the solvent in the first step can improve the wetting uniformity of the hard carbon system powder, shorten the convergence time, and improve the repeatability of the solid content determination.

[0068] The embodiments and / or implementation methods described above are merely preferred embodiments and / or implementation methods for implementing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any way. Any person skilled in the art may make some modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but these should still be regarded as the technology or embodiments that are substantially the same as the present invention. This document uses specific examples to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the methods and core ideas of this application. The above descriptions are only preferred embodiments of this application. It should be noted that due to the limitations of written expression, while there are objectively infinite specific structures, those skilled in the art can make several improvements, modifications, or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner. These improvements, modifications, changes, or combinations, or the direct application of the inventive concept and technical solution to other situations without modification, should all be considered within the scope of protection of this application.

Claims

1. A rapid method for determining and optimizing the solid content of kneaded materials, characterized in that, Includes the following steps: Step 1: Take samples proportionally according to the raw material ratio of the production line to obtain pilot raw materials; add solvent to the pilot raw materials in batches in a gradient, and perform stirring and state observation after each addition until the rheological properties of the slurry reach the preset target paste benchmark; calculate the initial solid content X% based on the dry weight of the pilot raw materials and the total amount of solvent added; the pilot raw materials include active main material, conductive agent and binder. Step 2: Using the initial solid content X% as the baseline offset, set the target solid content and inversely calculate the theoretical amount of solvent required to reach the target solid content; add the theoretical amount of solvent to the same mass of the small-scale raw materials as in step 1, stir, and perform state observation again; if the slurry state deviates from the target paste benchmark, perform step-by-step correction on the target solid content according to the actual deviation direction, and repeat the steps of calculating the theoretical amount of solvent, adding, and observing the state based on the corrected solid content until the slurry state reaches the target paste benchmark, and calibrate the current solid content as the reliable solid content Y.

2. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, In step one, the solvent is added in batches in a progressively decreasing manner. The initial addition is 60% to 70% of the estimated total solvent mass, and the remaining solvent is added in 2 to 3 batches, with each batch adding 10% to 25% of the estimated total solvent mass.

3. The rapid determination and optimization method for kneaded solids content according to claim 2, characterized in that, The remaining solvent is added in two batches, with the second batch accounting for 20% to 25% of the estimated total solvent mass and the third batch accounting for 10% to 15% of the estimated total solvent mass.

4. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, In step one, the solvent is added in multiple stages in a reverse incremental manner, specifically in three gradient stages: the first addition accounts for 15% to 25% of the estimated total solvent mass; The second addition accounts for 25% to 35% of the estimated total solvent mass; The third addition accounts for 40% to 60% of the estimated total solvent mass.

5. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, The target paste-like standard in step one is defined as follows: the slurry adheres to the stirring tool, flows in a viscous manner when poured, and has no lumps or stratification.

6. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, In step two, the step of performing a step-by-step correction of the target solid content based on the actual deviation direction is as follows: if the slurry exhibits clumping, loose granular form, or loses its adhesion to the stirring tool after a one-time addition of solvent, it is determined to be in an over-dry state, and the target solid content needs to be corrected downward by 0.1~0.3%; If the slurry exhibits liquid-solid stratification or free solvent precipitation after a single addition of solvent, it is determined to be in an overly dilute state, and the target solid content needs to be corrected upward by 0.1~0.3%.

7. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, In step one, the solvent added initially contains 0.3% to 0.8% of an organosilicon-modified polyether wetting and dispersing agent by the estimated total mass of the solvent. This dispersing agent is not added additionally in subsequent solvent additions.

8. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, The adhesive is an oil-based compound adhesive system, which is composed of polyvinylidene fluoride (PVDF) and polyimide (PI) powder. The mass ratio of PVDF to PI powder is 7.5:2.5 to 8.5:1.5, and the total mass of the adhesive accounts for 4.5% to 5.5% of the total mass of the raw materials in the pilot test.

9. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, The binder is an aqueous compound binder system, which is composed of sodium carboxymethyl cellulose (CMC) and sodium alginate powder. The mass ratio of CMC to sodium alginate powder is 6.5:3.5 to 7.5:2.5, and the total mass of the binder accounts for 4.5% to 5.5% of the total mass of the raw materials in the pilot test.

10. The rapid determination and optimization method for kneaded solids content according to claim 1, characterized in that, In step one, when the solvent is added in multiple batches, a silane coupling agent is mixed into the solvent added in the first batch. The silane coupling agent is selected from γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane, and its addition amount is 0.1% to 0.5% of the total mass of the raw materials in the pilot test. The solvent is deionized water or an aqueous solvent system.